Interdisciplinary practices in environmental education: paths to sustainability (Research, Society and Development, 2020)
Environmental Education is characterized as an integrated, continuous and permanent educational practice in the socio-environmental dimension and must be seen as a “transversal” theme, which can be addressed in the curricula of different areas of knowledge. It is essential to emphasize that right to quality education regarding environmental practices must be considered and prioritized in its development, as this will enable the consolidation of subsidies for the accomplishment of an effective and qualified work, that results in balance of the healthy environment for all life forms. The goal of this work is, through a theoretical approach, to bring to discussion the importance of interdisciplinarity in the context of Environmental Education and its contribution to the sensitization of the human being as part of the ecological system and to treat the theme in a systemic way, from the perspective of the set of Sustainable Development Goals-Agenda 2030. The method used was the inductive one, because from the relationship between particular basic statements, it allows to reach a general conclusion.Therefore, it can be inferred that the environmental dimension is configured as an issue that concerns a set of actors from the educational, pedagogical and substantial universe, enhancing the involvement of the various knowledge systems, necessary to promote the debate and the search for results, constituting the Environmental Education as an instrument for sustainable development.